Legal Pluralism and Divorce Practices in the Baduy Indigenous Community: Negotiating Customary and Islamic Law in Indonesia - Farhah Salsabila; Krismono Krismono; Mukhsin Achmad; Nizar Muh Faaruq Al Qudsi (Al-Syakhsiyyah: Journal of Law and Family Studies, 2026)
This study aims to analyze legal pluralism in divorce practices among the Baduy indigenous community in Kanekes Village, Lebak Regency, Banten, by comparing the Inner Baduy, Outer Baduy, and Islamic Baduy communities. The research focuses on the dynamics of the relationship between customary law and Islamic law in shaping patterns of acceptance of divorce within the indigenous community. This study is a field study employing a qualitative socio-legal approach. Data were collected through in-depth interviews, observations, and documentation of traditional leaders, religious figures, and the Baduy community. Analysis was conducted using a descriptive-interpretive approach to understand divorce practices within the context of traditional values, religion, and social change in the Baduy community. The results indicate varying levels of acceptance of divorce among the three communities. The Inner Baduy strictly uphold the prohibition against divorce as part of maintaining customary and communal harmony. The Outer Baduy demonstrate a more flexible pattern of adaptation through mediation and limited accommodation in divorce cases. At the same time, the Islamic Baduy are more inclined to follow Islamic legal principles that permit divorce as a last resort to avoid harm. Nevertheless, all communities continue to prioritize the integrity of the household as a core value. This study contributes to strengthening research on legal pluralism by demonstrating that the relationship between customary law and Islamic law is one of negotiation and adaptation rather than merely conflict.